2004
DOI: 10.1021/ic0497836
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Conformations of 2,2-Di-tert-butyl-1,3-diaza-2-silacyclopentane:  Gas Electron Diffraction and Quantum Chemical Calculations

Abstract: The geometric structure and conformational properties of the saturated five-membered-ring compound 2,2-di-tert-butyl-1,3-diaza-2-silacyclopentane, (t-Bu)(2)Si(NH)(2)(CH(2))(2), was investigated by gas electron diffraction and quantum chemical methods (B3LYP and MP2 with 6-31G basis sets). The compound exists as a mixture of two conformers, both possessing a twist conformation and C(2) symmetry. In the prevailing form (76(6) % at 305 K) the N-H bonds stagger the adjacent CH(2) groups, and in the minor form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…1 Two ways of interconversion of the axial (f = 01) and equatorial (f = 1801) conformers of pyrrolidine: pseudorotation (green, o300 cm À1 ) and ring inversion (red, B1500 cm À1 ). 6 resonance 11 and electron diffraction (ED) 11,12 enable the determination of energetic preferences and structures of lower pseudorotational states, however, information about the complete pseudorotational potential usually remains beyond their scope. The gas-phase ED study of the conformational preferences in pyrrolidine in conjunction with ab initio calculations indicated that the axial conformer is energetically the most stable one, 13 an assignment which was revised later by microwave spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Two ways of interconversion of the axial (f = 01) and equatorial (f = 1801) conformers of pyrrolidine: pseudorotation (green, o300 cm À1 ) and ring inversion (red, B1500 cm À1 ). 6 resonance 11 and electron diffraction (ED) 11,12 enable the determination of energetic preferences and structures of lower pseudorotational states, however, information about the complete pseudorotational potential usually remains beyond their scope. The gas-phase ED study of the conformational preferences in pyrrolidine in conjunction with ab initio calculations indicated that the axial conformer is energetically the most stable one, 13 an assignment which was revised later by microwave spectroscopy.…”
Section: Introductionmentioning
confidence: 99%